A retrospective study of the clinical management and treatment outcomes of patients established on antiretroviral therapy who are newly diagnosed with tuberculosis in the public sector, KwaZulu-Natal - Veerasami, Sowbagium (Stellenbosch : Stellenbosch University, 2013)
Thesis (MCurr)--Stellenbosch University, 2013.